(untitled) (Theatrum historiae, 2008)
The paper deals with the problem of symbolic personification within Czech national festivals in 1860s and 1870s. This period represents the peak of the Czech national upheaval in 19th century in form of mass public action of representatives of the national movement. During this identity-building and identity-inventing process the organisation of national festivals played one of the most important mobilizing roles. Symbolic context of Czech nationality was being re-invented by performing the festive culture as a space for communication and confrontation of new and old meanings. The process comprised the multi-level overlaying of different identities, e.g. regional, local, class, professional, religious, within the national frame. One aspect of these ritual enactments was integration of different important persons that were celebrated – creation of national Pantheon. The analysis in this article focuses on these perfomative acts (J. Butler) using historical and anthropological approaches based in concept of culture as “web of significance” (C. Geertz). Main goal is to show how meanings transfer from symbolic national frame to celebrated persons and vice versa. The analysis is done in four steps. Firstly, the symbolic personification is analysed in the case of celebrating Czech patriots active in pre-1848 period – "awakeners of dying Nation". Among these ones particular significance was given to František Palacký whose role as "the father of Nation" is interpreted in Christian context of family metaphors. Third section is dedicated to the personification of Hussite historical context with Jan Hus, Jan Žižka and Prokop Holý as main actors. Last part shows the examples of (mostly unsuccessful) attempts of introducing Catholic symbolism and identity in to the national frame during the saint’s-days of Slavic saints Cyril and Method.